Urbild und Abbild Untersuchungen zu Herrschaft und Weltbild in Altrußland 11.-16. Jahrhundert - Soldat, Cornelia (Slavistische Beitraege, 2001)
A culture shaped by Christianity is about deciphering its underlying religious figures. The present work aims to contribute to this. The point is to examine a figure that established the "functioning" of Old Russian culture, commonly referred to as "the neo-Platonic archetype-image-thinking". Implicitly it is assumed here that in the 10th and 11th an influence of the Slavic culture by the Byzantine Christianity of orthodox imprint took place, the exact way of which is not to be determined. The study of the image-of-the-image thinking in the Byzantine culture and its attachment to the icon worship is therefore dedicated to a first part of this work, the study of the ancient Russian archetype image thinking of the next and largest part.